PEMULIHAN PARIWISATA DI ERA PANDEMI COVID-19: PENYULUHAN PENGEMBANGAN DESA WISATA DI DESA TEMPUR, KABUPATEN JEPARA (Universitas Esa Unggul, 2022)
Tempur Village is a hidden village with beautiful natural scenery because it is located on the slopes of the Muria mountains. In the village of Tempur there are several potential tourism objects that have not been managed properly. During the Covid-19 pandemic, many cafes and food stalls in the village were closed due to lack of visitors. The purpose of this community service program is counseling about the development and tourism recovery in the era of the Covid-19 pandemic. The business partner in this program is ‘Pemuda Karang Taruna’. The method used to achieve the goal is a field survey, mapping the potential of tourism objects and counseling on the development of tourist villages based on the Covid-19 health protocol. After running this program, the Tempur Village community opened their minds and their knowledge related to the management of tourist villages. The type of tourist village that can be developed in the Tempur Village is an open-type tourist village based on natural beauty. Some of the potential tourist objects that can be developed are Bejangan Hill, Ombo River, Wind Temple, Waterfall, 'Hump Cow' Peak, paddy fields, and supporting infrastructure for tourist villages such as cafes and homestays. The tourism recovery in the Tempur Village during the Covid-19 pandemic is by implementing health protocols to suppress the rate of Covid-19, namely wearing masks, washing hands, and keeping a distance. The implication of this community service program is that the Tempur Village community has economic independence, and can realize their village as one of the leading tourist villages in Jepara Regency. Keywords: tourism village, tourism recovery, Covid-19 pandemic